2018
DOI: 10.1016/j.joca.2018.02.908
|View full text |Cite
|
Sign up to set email alerts
|

Targeting β-catenin dependent Wnt signaling via peptidomimetic inhibitors in murine chondrocytes and OA cartilage

Abstract: These data indicate that blockade of canonical Wnt signaling might be a therapeutic strategy to treat early OA cases and protect further cartilage degradation by preventing chondrocyte hypertrophic differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Additionally, SOX9 expression in chondrocytes is strictly controlled by other factors (e.g., HIF1α, miR-145, SOX5) [ 63 65 ]. Wnt signaling plays an important role during chondrogenesis and hypertrophic differentiation [ 43 ]. Multiple studies have shown that the genes encoding the Wnt signaling regulatory components GSK-3β, adenomatous polyposis coli, and Wnt3a are direct targets of miR-27b [ 66 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, SOX9 expression in chondrocytes is strictly controlled by other factors (e.g., HIF1α, miR-145, SOX5) [ 63 65 ]. Wnt signaling plays an important role during chondrogenesis and hypertrophic differentiation [ 43 ]. Multiple studies have shown that the genes encoding the Wnt signaling regulatory components GSK-3β, adenomatous polyposis coli, and Wnt3a are direct targets of miR-27b [ 66 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOX9 is a negative regulator of chondrocyte hypertrophic differentiation [42], and the β-catenin pathway is involved in controlling SOX9 expression [43]. Thus, we examined whether miR-27b enhanced SOX9 expression through the β-catenin pathway.…”
Section: Mir-27b Inhibits Hbmsc Hypertrophic Chondrocyte Differentiatmentioning
confidence: 99%
“…In this study, we found that Wnt-3-b-catenin pathway rather than Wnt10a was up-regulated with the OA grade. Previous studies showed that the Wnt pathway participated in a series of cell homeostasis processes, including cell differentiation, proliferation, migration and adhesion [22,23]. Further studies found that the Wnt pathway was inhibited in normal cartilage, whereas its activation promoted OA [23].…”
Section: Discussionmentioning
confidence: 99%
“…A promising recent reagent is SM04690 (Samumed), an inhibitor of WNT receptor binding that is now in a phase III clinical trial, which has been shown to elicit protective effects on cartilage during joint destruction in an acute cruciate ligament tear and partial medial meniscectomy rodent OA model [48]. Inhibition of β-catenin, an intracellular signal transducer of WNT, by StAx-35R inhibits chondrocyte phenotypic shifting of human OA cartilage explants, and has been reported to result in increased SRY-Box transcription factor 9 (SOX9) and aggrecan gene expression and decreased collagen type X α1 chain (COL10A1) gene expression [49,50].…”
Section: Traumamentioning
confidence: 99%